2011
DOI: 10.1364/oe.19.025441
|View full text |Cite
|
Sign up to set email alerts
|

Polarization independent Fabry-Pérot filter based on polymer-stabilized blue phase liquid crystals with fast response time

Abstract: This work demonstrates a polarization-independent electrically tunable Fabry-Pérot (FP) filter that is based on polymer-stabilized blue phase liquid crystals (PSBPLCs). An external vertical electric field can be applied to modulate the effective refractive index of the PSBPLCs along the optical axis. Therefore, the wavelength-tuning property of the FP filter is completely independent of the polarization state of the incident light. The change in the birefringence in PSBPLCs is governed by Kerr effect-induced i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…tens of milliseconds. BPLCs are therefore considered as a promising alternative to nematics for electro-optic applications, including: gratings [113][114][115], lenses [113,116], interferometric filters [117,118], attenuator [119] and displays [86,120,121]. Most of these devices are made of PSBPs because the addition of polymer network could suppress the slow electrostriction effect (cf.…”
Section: Optical Isotropy and Fast Electro-optic Responsementioning
confidence: 99%
See 1 more Smart Citation
“…tens of milliseconds. BPLCs are therefore considered as a promising alternative to nematics for electro-optic applications, including: gratings [113][114][115], lenses [113,116], interferometric filters [117,118], attenuator [119] and displays [86,120,121]. Most of these devices are made of PSBPs because the addition of polymer network could suppress the slow electrostriction effect (cf.…”
Section: Optical Isotropy and Fast Electro-optic Responsementioning
confidence: 99%
“…The PSBP can be integrated either inside or outside an optical cavity to realize an electrically tunable interferometric filter. By sandwiching a PSBP between two aluminium mirrors, a tunable Fabry-Pérot filter was thus fabricated [117]. Owing to the high reflectivity of the mirrors and optical transparency of the PSBP across an extremely broad spectrum, the etalon could be operated in both the visible and near infrared regions.…”
Section: Optical Isotropy and Fast Electro-optic Responsementioning
confidence: 99%
“…For this reason, polymer stabilization methods have frequently been employed to expand the temperature ranges at which cubic BPs can exist [3,[7][8]. Although polymer-stabilized (PS) BPI samples possessing wide temperature ranges (several tens of degrees Celsius), however, have been reported by several groups [8][9][10], such wide temperature ranges for PS simple cubic blue phase (PSBPII) samples have been rarely achieved [7]. This is because the temperature ranges in which a pure BPII appears are narrowly compared with those in which pure BPI appears, and as such, in situ polymerization is more difficult in BPII than in BPI.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the resonance wavelength of the LC-FP filter will be varied with the voltage driving-signal. It is reported that the electrically tunable LC-FP filter working in the visible [11,12] and near-infrared [13], has also been developed successfully.…”
Section: Introductionmentioning
confidence: 99%